Assessment of Antimicrobials' use in Pediatrics in Moradabad city - V, Jha; M, Abid; GP, Mohanta; A, Patra; Kishore, Kamal; NA, Khan (Indian Journal of Pharmacy Practice)
This study assesses the use of antibiotics in pediatric patients and also rationality & irrationality of prescriptions.The present study was a population based analytical epidemiological design in the settings of an urban population in Moradabad, (UP) India, during Jan 2009 to April 2009. The intended work can be divided into the following steps: by selecting the antibiotics prescribed prescription then divided the prescriptions according to the following criteria; category of antibiotic used, combination of antibiotic used, site of infection diagnosed & rationality and irrationality of prescriptions. It is important to determine and reduce the antibiotic use in children as it can cause resistance to antibiotics in them that can lead to different problems. The most common antibiotics prescribed in pediatric patients belong to the class of Quinolones (43.18%), among which Norfloxacin (28.95%) predominates. Amoxicillin + Clavulanic acid (40.74%) was the most frequently used antibiotic combination. It was concluded that maximum number of prescriptions were found rational based on considering the number of antibiotics per prescription and drug interaction, while irrational prescriptions were found to be less.
Keywords: antimicrobial drugs; hypersensitivity reactions; bacterial infection; rationality